1990
DOI: 10.1007/bf00127129
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic studies on wild house mice from Belgium

Abstract: The present status of Robertsonian karyotype variation in populations of wild mice from Belgium is presented. Two fusions, Rb(4.12)1Nam and Rb(5.10)3Nam, were identified in the central plain of this flat country. Surrounding this region only mice with the usual 2n = 40 karyotype occurred. From the distribution pattern some possible relationships to other Rb populations from Europe are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
1
11
0
6
Order By: Relevance
“…In mainland areas, the Rb races occur singly or in groups surrounded by the much more widely distributed standard race. The large majority of studies of chromosomal hybrid zones in the house mouse have focused on contacts between a Rb race and the standard race, such as those in Belgium (Hu$ bner & Koulischer, 1990 ;Bauchau et al, 1990), Denmark (Nance et al, 1990 ;Fel-Clair et al, 1996, northern Scotland (Searle, 1991 ;Wallace et al, 1992 ;Searle et al, 1993), central Italy (Castiglia & Capanna, 1999, northern Spain (Gu$ ndu$ z et al, 2001) and Tunisia (Saı$ d & Britton-Davidian 1991 ;Saı$ d et al, 1993Saı$ d et al, , 1999. These studies have shown that hybrid zones between the standard race and a Rb race with a high diploid number (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In mainland areas, the Rb races occur singly or in groups surrounded by the much more widely distributed standard race. The large majority of studies of chromosomal hybrid zones in the house mouse have focused on contacts between a Rb race and the standard race, such as those in Belgium (Hu$ bner & Koulischer, 1990 ;Bauchau et al, 1990), Denmark (Nance et al, 1990 ;Fel-Clair et al, 1996, northern Scotland (Searle, 1991 ;Wallace et al, 1992 ;Searle et al, 1993), central Italy (Castiglia & Capanna, 1999, northern Spain (Gu$ ndu$ z et al, 2001) and Tunisia (Saı$ d & Britton-Davidian 1991 ;Saı$ d et al, 1993Saı$ d et al, , 1999. These studies have shown that hybrid zones between the standard race and a Rb race with a high diploid number (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In Belgium the BBEL race characterised by 4.12 and 5.10, in Germany the DSTJ race with 5.15 and 13.14 and in Denmark the DKEA race with 2.5, 3.8 and 6.9 show staggered clines similar to those seen in the John o’Groats-standard hybrid zone, with intermediate homozygous forms at high frequency in parts of the hybrid zone [4,14,40,41,42,43]. As for the John o’Groats-standard hybrid zone, the degree of staggering of the different chromosomes differs according to the transect direction across the Belgian and German hybrid zones [40,41,42].…”
Section: Summary and Synthesismentioning
confidence: 97%
“…As for the John o’Groats-standard hybrid zone, the degree of staggering of the different chromosomes differs according to the transect direction across the Belgian and German hybrid zones [40,41,42]. In northern Italy, the most widely prevalent and presumably the first formed metacentric among chromosomal races there, 16.17, has a wider distribution than other metacentrics at the contact between the IBIN metacentric race and the standard acrocentric race [14,44].…”
Section: Summary and Synthesismentioning
confidence: 99%
“…a O rdered according to position of clines, with those centred closest to the centre of the metacentric race given first. b Hübner and Koulischer [1990]; Bauchau et al [1990]. c Searle et al [1993].…”
Section: Discussionmentioning
confidence: 99%
“…This was for zones in Belgium [Hübner and Koulischer, 1990;Bauchau et al, 1990], Northern Scotland and Central Italy [Spirito et al, 1980;Castiglia and Capanna, 1999] where quantitative clinal data were hitherto unavailable.…”
Section: Methodsmentioning
confidence: 99%